2020 IEEE Symposium on Security and Privacy (SP) 2020
DOI: 10.1109/sp40000.2020.00057
|View full text |Cite
|
Sign up to set email alerts
|

Plundervolt: Software-based Fault Injection Attacks against Intel SGX

Abstract: Dynamic frequency and voltage scaling features have been introduced to manage ever-growing heat and power consumption in modern processors. Design restrictions ensure frequency and voltage are adjusted as a pair, based on the current load, because for each frequency there is only a certain voltage range where the processor can operate correctly. For this purpose, many processors (including the widespread Intel Core series) expose privileged software interfaces to dynamically regulate processor frequency and op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
126
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(127 citation statements)
references
References 47 publications
(58 reference statements)
1
126
0
Order By: Relevance
“…There are other side-channels such as speculative execution [12], [17], [50], communication patterns [55], power analysis [54] and others [34], [41]. We note that these attacks can be mitigated by some complementary works [8], [16], [20], [56].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…There are other side-channels such as speculative execution [12], [17], [50], communication patterns [55], power analysis [54] and others [34], [41]. We note that these attacks can be mitigated by some complementary works [8], [16], [20], [56].…”
Section: Related Workmentioning
confidence: 99%
“…There exist some other side-channel attacks against TEEs. Particularly, those attacks are based on speculative execution [12], [17], [50], communication patterns [55], denialof-service [34], power analysis [54] and vulnerabilities in implementations [41]. Those attacks are out of the scope of OblivSketch.…”
Section: B Threat Modelmentioning
confidence: 99%
“…However, security researchers have shown that many of these isolation mechanisms can be attacked by means of software-exploitable side-channels. Such side-channels have been shown to violate integrity of victim programs [3], [4], [5], as well as their confidentiality on both high-end processors [6], [7], [8], [9] and on small microprocessors [10]. In fact, over the past two years, many major isolation mechanisms have been successfully attacked: Meltdown [7] has broken user/kernel isolation, Spectre [8] has broken process isolation and software defined isolation, and Foreshadow [9] has broken enclaved execution on Intel processors.…”
Section: Introductionmentioning
confidence: 99%
“…This technique essentially targets security critical embedded systems, using physical disturbances (e.g., laser rays, or electro-magnetic fields) to inject faults. However, it may now also concern much larger software classes when considering recent hardware weaknesses like the so-called Rowhammer attack [1], [2], or by exploiting some weaknesses in the power management modules [3], [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%